Design Implications for Human-Machine Interactions from a Qualitative Pilot Study on Privacy - Leschanowsky, Anna; Brueggemeier, Birgit; Peters, Nils (2021 ISCA symposium on security and privacy in speech communication, 2021, 2021)
There are only few qualitative studies investigating privacy in Human-Machine Interaction (HMI). We conducted an exploratory qualitative study with the aim to better understand factors that influence privacy in HMI and how they relate to privacy in Human-to-Human Interaction (HHI). From there, we derived recommendations that can help designers to promote informed decision making and improve data sharing processes. We discuss the main distinguishing factors that were found carrying out semi-structured interviews. First, HMI contexts miss flexibility and proper protection strategies such that users can not easily protect themselves similar to what they are used to in HHI. Second, users were able to easily evaluate benefits of sharing data while risks remained elusive and difficult to assess. Further research is needed to understand the impact of this imbalance on users’ informed decision making.<br